ПОКРАЩЕННЯ МАГНІТНОЇ ЧИСТОТИ МІКРОСУПУТНИКА ІЗ НЕВИЗНАЧЕНОСТЯМИ НА ОСНОВІ КОМПЕНСАЦІІ ПРОСТОРОВИХ ГАРМОНІК МАГНІТНОГО ПОЛЯ - Кузнецов, Б.І.; Нікітіна, Т.Б.; Бовдуй, І.В.; Чуніхін, К.В.; Коломієць, В.В.; Кобилянський, Б.Б. (Інститут електродинаміки НАН України, Київ, 2025)
Problem of microsatellite magnetic cleanliness (MMC) improving by magnetic field (MF) spatial harmonics compensation and magnetic characteristics uncertainty (MCU) sensitivity reducing considered. Prediction and control by uncertain microsatellite MC design are geometric inverse magneto static problem (GIMSP) reduced to vector game solution. Vector payoff calculated based on development method for analytical calculation of magnetostatic field induction of spherical sources in the Cartesian coordinate system (CCS) using Wolfram Mathematica ® software. Both vector game solution calculated based on particles multi-swarm optimization (PMSO) algorithms from Pareto optimal solutions taking into account binary preference relations. Prediction model and location of compensating units in spherical coordinates as well as multipole harmonic coefficients of dipoles, quadrupoles and octupoles are calculated during prediction and control of uncertain microsatellite MC. Results of MC improving for microsatellite «Sich» family by compensation of dipoles, quadrupoles and octupoles components of initial MF spatial harmonics and reducing sensitivity to MCU are given. References 17, figures 2.